Implementasi Metode Content Based Filtering Pada Aplikasi Pencarian Taman Penitipan Anak - Yaya Sudarya Triana; Fryda Farizha Adrianti; Fitri Anggri Maharani (Ikatan Ahli Informatika Indonesia (IAII), 2019)
Economic demands make working mothers currently a trend in society, especially in DKI Jakarta. The dual role of a mother makes it difficult for them to divide the time to take care of the child, especially if the child is still at the age of a toddler. Along with this, the existence of a Daycare is increasingly needed as an alternative parents to take care of their children while they are working. Therefore, in this study a web-based Daycare search application will be created that can help parents search for Daycare in DKI Jakarta. This application uses the Content Based Filtering method that is by providing recommendations based on the similarity of criteria between Daycare that are being seen in detail by Parents and Daycare who have been given a rating by them with other Daycare available in the system so that it can be a comparison for Parents in choosing Daycare. The results obtained from this study are made with an application that applies the Content Based Filtering method that supports the